2001
DOI: 10.1021/jf000776j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Identification of Bacterial Strains By Fourier Transform Near-Infrared Spectroscopy

Abstract: The use of Fourier transform near-infrared (FT-NIR) spectroscopy and multivariate pattern recognition techniques for the rapid detection and identification of bacterial contamination in liquids was evaluated. The complex biochemical composition of bacteria yields FT-NIR vibrational transitions (overtone and combination bands) that can be used for classification and identification. Bacterial suspensions (Escherichia coli HB101, E. coli ATCC 43888, E. coli 1224, Bacillus amyloliquifaciens, Pseudomonas aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 22 publications
1
107
0
4
Order By: Relevance
“…Studies have shown that FTIR spectra can be used to identify and differentiate microorganisms down to the level of subspecies, strain, or even serotype (46)(47)(48)(49). The technique produces a complex spectral fingerprint of intact microbial cells that reflects the total biochemical composition of the microorganism.…”
Section: Identification Of Microbial Strainsmentioning
confidence: 99%
“…Studies have shown that FTIR spectra can be used to identify and differentiate microorganisms down to the level of subspecies, strain, or even serotype (46)(47)(48)(49). The technique produces a complex spectral fingerprint of intact microbial cells that reflects the total biochemical composition of the microorganism.…”
Section: Identification Of Microbial Strainsmentioning
confidence: 99%
“…It has already been reported that using Fourier Transform Spectroscopy identification of bacteria and other microorganisms to the level of species is possible in the near-and mid-IR [10,11]. At the same time many benefits may result fro m experimental observations of spectroscopic features in the sub-THz reg ion that was not yet widely exp lored.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphate and thiosulphate reducing bacteria Genus FTIRS, FTIRS-ATR HCA, PCA [16,17] Alicylobacillus Genus FTIRS PCA, SIMCA [20] Strain FTIRS-HATR LDA, PCA [75] Photorhabdus Genus FTIRS-ATR HCA, PCA [18] Xenorhabdus Genus FTIRS-ATR HCA, PCA [18] Arcanobacterium Genus FTIRS ANN [19] Actinomyces Genus FTIRS ANN [19] Trueperella Genus FTIRS ANN [19] Species FTIRS ANN [19] Bacillus Genus FTIRS PCA, SIMCA [20] Species FTIRS, FTIRS-ATR, Diffuse Reflectance-FTIRS PCA, HCA, DFA, CVA, SIMCA [26][27][28][29][30]49,50,54,55] Vegetative/Sporulated FTIRS PCA, CART [83] Escherichia Genus FTIRS-ATR HCA, PCA [18] Species FTIRS, FTIRS-ATR HCA, ANN, PCA, SIMCA, CVA [49][50][51][52][53][54]86,92] Escherichia coli Sequence type FTIRS, FTIRS-ATR PC-DFA, PLSDA, HCA, SIMCA [67,68] Strain FTIRS PCA, SIMCA, CVA [49,50,52,73] MLVA profile FTIRS HCA, CVA [72] Listeria spp. Species FTIRS, FTIRS-ATR, FTIR microspectroscopy CVA, ANN, SCDA, PLSRDA, PCA [5,[21][22][23][24][25]…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
“…Species FTIRS, FTIRS-ATR, FTIR microspectroscopy CVA, ANN, SCDA, PLSRDA, PCA [5,[21][22][23][24][25]27,49,50] Lactobacillus spp. Species FTIRS HCA, ANN [31,32,39,40,53] Enterococcus spp.…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%